2000
DOI: 10.1021/bi0003240
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Active Site of Saccharomyces cerevisiae Dolichyl-Phosphate-Mannose Synthase Using Fluorescent Labeled Dolichyl-Phosphate Derivatives

Abstract: Dolichol-phosphate mannose (Dol-P-Man) is a key mannosyl donor for the biosynthesis of N-linked oligosaccharides as well as for O-linked oligosaccharides on yeast glycoproteins, and for the synthesis of the glycosyl-phosphatidylinositol anchor found on many cell surface glycoproteins. It is synthesized by Dol-P-Man synthase which is the only glycosyltransferase in the dolichol pathway that has been expressed as an active protein, solubilized and purified in large enough quantities for structural investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…In particular, we demonstrated that the transfer of Man from the mycobacterial C 50 / C 40 /C 35 [23]. In the present study, we reproduced these assays using mannosylated probes, generated via recombinant Mt-Ppm1/ D2, as the radiolabelled Man donor.…”
Section: Probe-p[ 14 C]man Act As Sugar Donors For a Mycobacterial α(supporting
confidence: 53%
See 3 more Smart Citations
“…In particular, we demonstrated that the transfer of Man from the mycobacterial C 50 / C 40 /C 35 [23]. In the present study, we reproduced these assays using mannosylated probes, generated via recombinant Mt-Ppm1/ D2, as the radiolabelled Man donor.…”
Section: Probe-p[ 14 C]man Act As Sugar Donors For a Mycobacterial α(supporting
confidence: 53%
“…The results were very gratifying in relation to substrate specificity and photoinhibition. All ten probes were excellent substrates for the PPM synthase, illustrating that changes within the lipid portion [22], such as overall chain length, saturation, unsaturation, benzyl and cyclohexyl rings, are tolerated without a substantial decrease in activity [22,[35][36][37] (Table 1). Probe 7 yielded the best activity for the PPM synthase assay (Table 1), presumably representing an optimum in terms of hydrophobicity and solubility of the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby Dpm1 can interact with both, the water-soluble mannosyl donor substrate GDP-Man in the cytosol and the highly hydrophobic mannosyl acceptor Dol-P within the ER membrane. Up to date, the three-dimensional (3D) crystal structure of yeast Dpm1 has not been resolved, however, usage of Dol-P and synthetic Dol-P analogs containing a fluorophore group provided a 3D structural model of the enzyme with bound GDP-Man, Dol-P and Mg 2+ ions to trace substrate binding and catalytic sites [36,37]. A two-domain structure was predicted with an N-terminal domain, which is made up of parallel ß-strands, and a C-terminal domain consisting of antiparallel ß-strands, each flanked by α-helices on both sides.…”
Section: The Mannosyl Donor Dolichol Phosphate-mannosementioning
confidence: 99%